MOSLEM UNDERGRADUATED STUDENT ENTREPRENEURIAL PREFERENCE: PAST PROFILE - Eka Tresna Gumelar (Universitas Islam Bandung, 2023)
The concept of entrepreneurship is still a debate whether it needs to be taught in formal education or not, but all agree that an entrepreneur is one of the economic drivers of a nation. The purpose of this research is to investigate student entrepreneur profile based on their past experiences especially among Moslem student using past profile self-assessment of Timmons and Spinelli Jr. The research used a quantitativemethodological approach. Questionnaires were sent out to respondents selected by the researcher using purposive sampling method. The results showed that the students placed capital such as personal savings, bank loans or investor funds, as the most important preference in their entrepreneur profile, is very logical for entrepreneurs who want to become the owner of a new business. In other hand, status and prestige were the last reasons in building their business. This shows that all students consider there is no relationship between entrepreneur status and the decision to become an entrepreneur.